Web-based Fuzzy Expert System for Diabetes Diagnosis - Mujawar, I.K; Jadhav, B.T (International Journal of Computer Sciences and Engineering, 2019)
The proposed work presents an outline and execution of online fuzzy expert system for diabetes diagnosis (WebFESDD). This work proposes a rule-based expert system where fuzzy logic was used. It was actualized online for the determination of diabetes disease using open source development environment. Doctors, diabetes experts and patients can utilize Web- FESDD for diabetes diagnosis as an intelligent diagnostic system. Fuzzy expert systems are able to handle imprecise data which occurs in process of disease diagnosis and treatment. Fuzzy Logic is highly suitable and applicable in designing expert systems in medicine context; especially in disease diagnosis procedure and in treatment plan. Open source programming advancement features and conditions were utilized to create and complete the proposed work.